Biofilmes e enzimas sintetizados no processo de degradação do tereftalato de polietileno (pet) por bacillus subtilis e phanerochaete chrysosporium - Jara, Alícia Maria Andrade Torres (2007)
In recent years, the consumption of the poly ethylene terephtalate plastic - PET is used in the manufacture of bottles, comes increasing in Brazil. PET is a polar thermoplastic, with raised dimensional stability and temperature of fusion, high impermeability the acid gases and chemical resistance to solvents. The biodegradation has been described as a possible methodology to reduce the accumulation of plastics. In this work it was carried through the evaluation by Bacillus subtilis and Phanerochaete chrysosporium performance on the biodegradation of the polyethylene terephtalate. In this direction, particles of polymer were submitted to the treatments: exposition to ultra violet light (6 and 36 hours) and temperatures (35ºC and 50ºC), followed incubation with the microorganisms during 30 and 60 days. The polymer degradation process was accompanied by determination of pH, biofilm formation and the cells viability, enzymes detection (amylase, protease, esterase, and polyphenoloxidase), as well as the scanning electron microscopy of biofilm and toxicity tests. The results obtained observed the biofilm formation by Bacillus subtilis on polyethylene terephtalate surface particles. The treatment using the temperature of 50ºC demonstrated a higher alteration in the surface of the polymer, supported the colonization of the microorganisms followed of the hydrolytic enzymes production. It was observed that Bacillus subtilis does not produced polyphenoloxidase. The results indicated the temperature (50º.C), induces the esterase production and it is related to degradation process. The P. chrysosporium produced esterases and polyphenoloxidase, whose enzymes had demonstrated to be involved with the polyethylene terephtalate degradation process, and were formed products with higher toxicities to Artemia salina